2016
DOI: 10.2135/cropsci2016.02.0128
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Genetic Diversity in the Origins of Pepper (Capsicum spp.) and Comparison with Worldwide Variability

Abstract: Several attempts in recent decades have been devoted to investigating the genetic and phenotypic diversity harbored by the genus Capsicum. Particular efforts have been directed to old varieties or landraces. However, the genus is still under‐researched, and further investigations that accurately define the relationships among species and identify those geographic regions with greater variability are required. In the present work, 107 Capsicum landraces from Ecuador, Peru, and Bolivia were evaluated with a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 69 publications
2
18
0
1
Order By: Relevance
“…The phylogenetic analysis using rDNA-ITS almost agreed with previous studies using molecular markers [15,16,[18][19][20] and DNA barcoding [8] with sequences except rDNA-ITS in terms of the formation of species clades and phylogenetic relations, although rDNA-ITS could not differentiate between C. chinense and C. frutescens. The analysis using molecular markers or DNA barcoding except rDNA-ITS requires many Capsicum species for species identification, and thus takes a lot of effort.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The phylogenetic analysis using rDNA-ITS almost agreed with previous studies using molecular markers [15,16,[18][19][20] and DNA barcoding [8] with sequences except rDNA-ITS in terms of the formation of species clades and phylogenetic relations, although rDNA-ITS could not differentiate between C. chinense and C. frutescens. The analysis using molecular markers or DNA barcoding except rDNA-ITS requires many Capsicum species for species identification, and thus takes a lot of effort.…”
Section: Discussionsupporting
confidence: 84%
“…In recent years, phylogenetic studies have been conducted to elucidate the relationship between Capsicum species based on molecular markers, including isozyme [16], random amplified polymorphic DNA [15], amplified fragment length polymorphism [17], simple sequence repeat [18,19], and single nucleotide polymorphism [20]. These studies analyzed the relationships between cultivated species, and indicated the species-specific clades formed; the species belonging to the C. annuum complex were genetically close to each other in phylogenetic trees.…”
Section: Introductionmentioning
confidence: 99%
“…C. frutescens accessions constituted the most homogenous group, except for PI224427. That accession was misclassified in a previous work that genetically placed it as more closely related to C. chinense [11]. Current data, based on fruit morphology and biochemical composition, confirmed that accession PI224427 should be ascribed to the C. chinense group.…”
Section: Discussionmentioning
confidence: 52%
“…For the sake of clarity, the accession PI585278 from the Galapagos Islands was considered within the Coastal region. This collection was previously characterized for genetic diversity and molecular markers linked to disease resistance and pungency-related traits [11,67]. The forty-eight landraces were cultivated during 2017 in an experimental field at the Technical University of Machala (Machala, El Oro, Ecuador) (03 • 16 S, 79 • 54 W).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation